Efektivitas model PBL berbantuan komik digital terhadap kemampuan penyelesaian soal cerita matematika - Pratama, Muhammad Wahyu Adi; Sutriyani, Wulan (Universitas PGRI Semarang, 2025)
Mathematical story problems are questions with a higher level of difficulty compared to using mathematical models directly. Many students encounter obstacles when understanding and solving story problems. Innovation of learning models and media is essential to develop students' capabilities in resolving mathematical story problems. The model and media that are usable PBL assisted with digital comics. This ressearch was undertaken to asses effectiveness PBL assisted by digital comics on students' abilities in solving story problems. This ressearch applies a statistical framework through the single-group pretest-posttest experimental method. Participant within this research were 24 students of grade 3 of SDN 3 Dermolo. The sample selection technique in this study applied saturated sampling. Data were analyzed through normality testing, homogeneity testing and paired sample t-test. Results obtained from paired sample t-test showed a Sig (2-tailed) value = 0.000, which means it under 0.05. T-count amount obtained was -5.987, which means it exceeded the t-table of 1.717. This research shows the implementing PBL assisted by digitals comics can enhance students' skill in solving story problems. The improvement is observable through the results of the pre-test, post-test and the results of the paired sample t-test which increased.